The Implementation of Multifunctional Boards to Improve Self-Confidence and Learning Outcomes on Mathematics - Mugiawati, Wawat; Kurniawan, Rudy; Rohaeti, Euis Eti (IKIP Siliwangi, 2025)
Self-confidence is an important thing in learning life so that it can be consistent and encourage good learning outcomes However, this can be relatively low for students, especially those learning lowest common multiple and highest common factor mathematics The aim of this research is to examine the use of multifunctional blackboard media to influence students' self-confidence and learning outcomes. This research was conducted on class IV students at MIN 21 Jln Rawa Kuning, East Jakarta. The research method used is quasi-experimental research (Quasi-Experiment) with a Nonequivalent control group design The population of this study was 60 grade IV students at MIN 21 East Jakarta, data collection regarding learning outcomes in the form of a multiple choice objective test of 30 questions with four alternative answers which were previously tested to test the validity and reliability of the question items. The conclusion of this research is that learning using multifunctional board media which is used well as a medium for learning can influence students' self-confidence because they can learn mathematics in a fun way which ultimately can influence mathematics learning outcomes well on lowest common multiple and highest common factor material. The conclusion of this research is that learning using multifunctional board media which is used well as a medium for learning can influence students' self-confidence because they can learn mathematics in a fun way which ultimately can influence mathematics learning outcomes well on Lowest Common Multiple and Highest Common Factor material. Hopefully this research can become a reference for other writers and can continue to develop knowledge in mathematics learning so that it can continue to improve the hard skills and soft skills of students.